Effects of human immunoglobulin A on Cryptococcus neoformans morphology and gene expression - Nuria Trevijano-Contador; Haroldo C. de Oliveira; Claudia Malacatus-Bravo; Varona Sarai; Isabel Cuesta; Marcio L. Rodrigues; Óscar Zaragoza; Liise-anne Pirofski (Microbiology Spectrum)
ABSTRACT Human IgM was previously shown to inhibit Titan-like cell formation of Cryptococcus neoformans, whereas IgG did not. Here, we conducted an in-depth analysis of the effect of normal human IgA on C. neoformans biology (strain H99) and compared it to that of IgG and IgM. We found that like IgM, IgA affected H99 cell size and morphology. The total size of cells cultured with IgA was significantly smaller at 24 h than cells cultured with IgM and IgG and comparable to IgM but smaller than IgG at 72 h. We also examined extracellular vesicle (EV) production and found that it was significantly reduced in cells cultured with IgA than the control, but the EVs were larger. To further probe the effect of IgA on H99, we performed expression profiling by RNAseq of H99 cells cultured with each immunoglobulin isotype and compared the results with IgA to those with IgM, IgG, and a control (PBS). These comparisons showed that cells cultured with IgA overexpressed genes related to cell rescue, defense, virulence, energy conservation, adapation to stress with CNAG_00735 (aldehyde dehydrogenase family seven member A1) being the most overexpressed, and repressed some genes related to vesicular transport, including CNAG_04306 (vesicle transporter SFT2B) and CNG_00063 (histone H3). Collectively, our findings suggest that the effects of IgA on cryptococcal biology deserve further investigation, as they reveal new insights into human host–C. neoformans interaction, which suggest that antibody responses may affect gene expression in C. neoformans.IMPORTANCEProfound CD4 T cell deficiency is associated with the development of cryptococcosis in HIV-infected individuals. However, perturbations in antibody immunity, including reduced levels of plasma IgA and IgM, have also been associated with cryptococcal disease status. While IgM has been studied in some detail, IgA has not. Here, we evaluated the effect of normal human IgA on Cryptococcus neoformans biology and morphology to expand knowledge of the role that it may play in cryptococcal pathogenesis.